2002
DOI: 10.1016/s0022-5347(05)64661-7
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Resection For Bladder Cancer Using 5-Aminolevulinic Acid Induced Fluorescence Endoscopy Versus White Light Endoscopy

Abstract: The risk of residual tumor after transurethral resection of transitional cell carcinoma is significantly decreased by 5-aminolevulinic acid fluorescence endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 23 publications
3
31
0
8
Order By: Relevance
“…19). Of the 16 HR-NMIBC patients with residual disease at the first check after initial GQ-PDDTURBT, 1 migrated from a Ta primary tumor to T1, whereas 2 patients had a stage migration from T1 to T2 (ie, 2 of 66 [3%] and were therefore recommended radical treatment).…”
Section: Resultsmentioning
confidence: 99%
“…19). Of the 16 HR-NMIBC patients with residual disease at the first check after initial GQ-PDDTURBT, 1 migrated from a Ta primary tumor to T1, whereas 2 patients had a stage migration from T1 to T2 (ie, 2 of 66 [3%] and were therefore recommended radical treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Zur Diagnose dieser entdifferenzierten Tumore haben sich mit einer hohen Sensitivität von ca. 90% die Urinzytologie als Goldstandard und die photodynamische Diagnostik (PDD) etabliert [2,4] Als positives Ergebnis wurde eine Anfärbung der Zellkerne und/oder des Zytoplasmas mit p16INK4a gewertet. Es erfolgte die quantitative Bestimmung der gefärbten Zellen bezogen auf die Gesamtzahl der Zellen in 10 "high power fields" (HPF).…”
Section: Originalien Hintergrund Und Fragestellungunclassified
“…Die photodynamische Diagnostik, z. B. mit Hexvix®, verbessert die Sensitivität der endoskopischen Methode [2,4]. Allerdings ist die Zystoskopie invasiv und man kennt Komplikationen wie Infektionen und Blutungen.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…In 2001, Riedl et al [22] first reported a significant reduction of residual tumor rate in 102 patients, finding remnant tumor at second-look TURB in 16% and 39% of PDD and WL cases, respectively (P = 0.005). One year later, Kriegmair et al [23] found PDD to significantly decrease residual tumors in 129 patients, as 62% and 41% were resected tumor-free at primary resection by PDD and WL, respectively (P < 0.014). Filbeck et al [24] confirmed these findings in the largest study on residual tumors to date, with a residual tumor rate of 4.5% and 25.2% in PDD versus WL, respectively (P < 0.0001), in 191 patients.…”
Section: Topical Application: a Giant Leapmentioning
confidence: 99%